2018
DOI: 10.5958/2231-6744.2018.00058.0
|View full text |Cite
|
Sign up to set email alerts
|

Betaine Supplementation and Milk Production during Heat Stress in Crossbred Cows

Abstract: Twenty crossbred cows (HF × Jersey) yielding 18-20 kg milk/d were divided into two groups of ten each based on milk yield, fat% and stage of lactation during hot summer months. The animals in both the groups were fed basal diet comprising 9.0 kg concentrates, 25.0 kg green fodder and 3.5 kg dry fodder. In addition to basal diet, animals in experimental group were supplemented with betaine hydrochloride @ 30 g/d and buffer @ 100 g/d for 90 d. The average temperature-humidity index was 71.78 and 78.12 at 09: 00 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
2
1
0
Order By: Relevance
“…Higher water intake in BET fed animals is also in agreement with Hall et al (2016). Higher DMI as noticed in our experiment substantiate the earlier findings of Shankhpal et al (2018) and Deshpande et al (2020) who also reported higher DMI which positively correlated with ADG in BET supplemented animals. However, the same is in partial agreement with Hall et al (2016), who reported a higher DMI Blood biochemical indices are considered a key indicator of animal health status.…”
Section: Discussionsupporting
confidence: 92%
“…Higher water intake in BET fed animals is also in agreement with Hall et al (2016). Higher DMI as noticed in our experiment substantiate the earlier findings of Shankhpal et al (2018) and Deshpande et al (2020) who also reported higher DMI which positively correlated with ADG in BET supplemented animals. However, the same is in partial agreement with Hall et al (2016), who reported a higher DMI Blood biochemical indices are considered a key indicator of animal health status.…”
Section: Discussionsupporting
confidence: 92%
“…The general homeostatic responses to thermal stress in mammals included elevated respiration rate and heart rate, reduced feed intake, profuse sweating, panting, and drooling of saliva (Silanikove, 1992). The results of our study in in rectal temperature and pulse rate were agreement with reported by Shankhpal et al (2018) who reported that supplemental betaine (30 g/day) significantly decreased the rectal temperature and pulse rate at 14:00 hr. as compared to control group in crossbred cows.…”
Section: Accordingsupporting
confidence: 91%
“…Thermal stress decreases growth rate due to reduction in feed intake and decreased nutrients availability (Lough et al 1990). Similarly, DMI in betaine supplemented crossbred lactating cows was higher (P<0.01) by 8.79% as compared to control (Shankhpal et al 2018). The DMI showed positive correlation with GH, ADG, BW and body measurements and negative correlation with THI, RT, ST, PR, NEFA and cortisol (Table 6).…”
Section: Dry Matter Intake (Dmi)mentioning
confidence: 81%